Inertia Force Identification of Cantilever under Moving-Mass by Inverse Method - Qiang Chen; Hao Yan; Minzhuo Wang; Haonan Ye (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper, a recursive inverse method is applied to solve the identification problem of inertia force between the cantilever and moving mass. The recursive inverse method consists of two parts: Kalman filter and recursive least-square algorithm. The basic Euler-Bernoulli beam model is introduced. Then, the differential equations and the state space model of the modal responses and the inertia force can be obtained. Finally, the recursive inverse method, which is based on the discretized state function of the system, is adapted. The identification results show that the recursive inverse method is suitable to be adapted in this problem. Some characteristics of the identification results are discussed and some further conclusions are reached. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1649